Aerodynamic and Pedestrian-Level Wind Characteristics of Super-Tall Buildings with Various Configurations. (2017) - Tamura, Yukio; Xu, Xiaoda; Tanaka, Hideyuki; Kim, Yon Chul; Yoshida, Akihito; Yang, Qingshan
Abstract: Recent super-tall building design has been released from the spell of compulsory symmetric shape design, and freestyle design is increasing. This is mainly due to architects' and structural designers' challenging demands for novel and unconventional expressions. Another important aspect is that rather complicated sectional shapes are basically good with regard to aerodynamic properties for cross-wind responses. A series of wind tunnel tests have been carried out to determine aerodynamic performance and pedestrian-level wind characteristics of many super-tall buildings with various configurations: square plan, rectangular plan, elliptic plan, with corner cut, with corner chamfered, tilted, tapered, inverse tapered, with setbacks, helical, openings and so on. Dynamic wind-induced response analyses of these models have also been conducted. The results of these tests have led to comprehensive discussions on the aerodynamic and pedestrian level wind characteristics of various tall building configurations.